Recycling of siliceous by-products to reduce their impacts on the environment - Bouabdallah, Soufiane; Chaib, Abdeslam; Bounouala, Mohamed; Dovbash, Nadiia; Benselhoub, Aissa; Bellucci, Stefano (Technology audit and production reserves, 2023)
Currently, there is a tendency to use less silica rich ores given the depletion of high-quality resources. The raw kaolin treatment of Tamazert (Eastern Algeria) produces, by hydrocyclone process, approximately 80 % of siliceous by-products. These siliceous wastes, which are stored in the open air, constitute a significant environmental problem. This research work aims to improve the quality of siliceous by-products, more particularly, to a process for the elimination of iron oxides and aluminum to make this raw material usable industrially as well as solving environmental issues. The collected by-products, were characterized by different techniques, such as X-ray fluorescence (XRF) and X-ray diffraction (XRD). XRF confirmed that the by-products east siliceous, with content going up to 82 % of SiO2. The by-product resulted from the raw kaolin treatment, mainly contains varying amounts of impurities such as iron oxide, titanium oxide and alumina. In all cases, the presence of these impurities affects the color and the physical properties of the mineral, and so lowers the economic value and limits the industrial application. In this framework, the classified fraction (–500)–(+100) µm was directed to attrition scrubbing followed by magnetic separation technique and chemical treatment by sulphuric acid with different concentrations. The results of the beneficiation tests of by-product indicate that using the attrition scrubbing alone not provides a suitable product for glass manufacture. The magnetic separation was tested with attrition on the useful fraction ((–500)–(+100) μm). The non-magnetic attritional fraction concentrates less than 0.45 % of Al2O3 and 0.05 % of Fe2O3. This low content coupled with a remarkable percentage in silica of 97.98 %.The tests by attrition and leaching with 40 % of sulphuric acid show, on the one hand, significant results with a high percentage of silica (>98.5 %) against 0.04 % Fe2O3 and 0.66 % Al2O3 ,and on the other hand, that the enriched product meets the standards required by glass making.